EFEKTIVITAS MODEL ELEVASI KEPALA ANTARA 30º DAN 45º TERHADAP PENINGKATAN SATURASI OKSIGEN PADA PASIEN STROKE ISKEMIK DI RSUD dr.MM. DUNDA KABUPATEN GORONTALO - Abdul Wahab Pakaya; Nurliah Nurliah; Iske Silfan R Paudi (Universitas Muhammadiyah Gorontalo, 2020)
Stroke is a cerebrovascular disease which occurs suddenly and causes neurological damage. This research was implemented to stroke patients at RSUD dr.MM.dunda, which aimed to find out the Effectiveness of head elevation models between 30° and 45° to increase oxygen saturation. The design used quasy experiment with non randominize pretest posttest contro group design approach. The samples were 22 respondents who are treated with head elevation between 30 ° and 45 ° for 4 weeks. Statistical test result obtained p value 0,000 less than alpha (p<0,05) means that Ho rejected, concluded that there is the influence of the elevation on increasing oxygen saturation and more influenced the 30° head elevation models to increase oxygen saturation in ischemic stroke patients at RSUD dr.MM.Dunda Limboto.